STUDI KONSISTENSI PERENCANAAN DAN PENGANGGARAN PEMBANGUNAN MANUSIA DI KABUPATEN KARANGASEM - Sonia Rakhma Maulani (Jurnal Administrasi Publik, 2022)
Consistency between planning and budgeting plays a vital role in ensuring the realization of regional development goals. This research aims to measure the level of consistency between human development planning and budgeting in Karangasem Regency during the period of 2017-2020 as well as identify the factors that influence these achievements. The results showed that the level of consistency was "very satisfactory" in the aspect of program nomenclature, but "very lacking" in the aspect of program performance indicators. In addition, the number of programs with a high ceiling deviation between planning and budgeting also tends to increase. These achievements are influenced by the politics of budgeting, the level of understanding among human resources, regional financial conditions, limited time for planning and budgeting and the use of information technology.